Implantable loop recorder as a strategy following cardiovascular implantable electronic device extraction without reimplantation. Issue 7 (1st June 2022) - Birs, Antoinette; Darden, Douglas; Eskander, Michael; Pollema, Travis; Ho, Gordon; Birgersdotter‐Green, Ulrika
Abstract: Background: Limited data exists for outcomes in patients undergoing cardiovascular implantable electronic device (CIED) transvenous lead extraction (TLE) without clear indications for device reimplantation. The implantable loop recorder (ILR) may be an effective strategy for continuous monitoring in select individuals. Objective: This retrospective analysis aims to investigate patients who have undergone ILR implant following TLE without CIED reimplantation. Methods: Clinical data from consecutive patients who have undergone TLE with ILR implant and without CIED reimplantation from October 2016 to May 2020 at a single center were collected. Results: Among 380 patients undergoing TLE, 28 (7.7%) underwent ILR placement without CIED reimplantation. TLE indications were systemic infection ( n = 13, 46.4%), pain at the site ( n = 8, 28.6%), device/lead malfunction ( n = 4, 14.2%), and other. Devices extracted included: dual‐chamber and single‐chamber pacemaker ( n = 14, 50%; n = 4, 14.2%), dual‐chamber implantable cardiac defibrillator ( n = 10; 35.7%), and cardiac‐resynchronization therapy with defibrillator ( n = 1, 3.5%). Reasons for no reimplantation included no longer meeting CIED criteria ( n = 14, 50%), patient preference ( n = 9, 32.1%), and no clear or inappropriate indication for initial CIED implantation ( n = 5, 18%). During an average of 12.3 ± 13.1 months of follow‐up, there were no lethal arrhythmias, and four (13.3%) patients underwent permanent pacemaker reimplantation due to symptomatic sinus bradycardia and atrioventricular block with syncope as discovered on ILR. Three patients died due to unknown causes ( n = 1), noncardiac ( n = 1), and acute coronary syndrome ( n = 1). Conclusions: In patients undergoing TLE without reimplantation, an ILR may be an effective monitoring strategy in patients at low risk for cardiac arrhythmia.